1976
DOI: 10.1029/gl003i002p00084
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional model of seismic velocity variation in the Earth's mantle

Abstract: Three dimensional velocity models for the earth's mantle were obtained satisfying P, S and some PcP and ScS travel time anomalies from deep focus earthquakes. A method of successive approximation was used to compute the uniform relative velocity perturbation over three dimensional blocks of size 10°×10° in longitude and latitude, and 500 km in thickness. Features of these velocity perturbations indicated that lateral heterogeneity is the most pronounced in the upper mantle and near the core‐mantle boundary. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…Initial investigations of aspherical structure in the lower mantle utilized moderate-sized (hundreds to a few thousand) sets of travel time anomalies (e.g., Sengupta and Toksoz, 1976) or differential travel time observations (e.g., Jordan and Lynn, 1974;Lay, 1983) to detect systematic variations relative to standard one-dimensional models. The main challenges in resolving lower mantle heterogeneity involve the uncertainty in earthquake source locations (typically, these are approximated by solving the location problem assuming a one-dimensional velocity structure, which intrinsically leads to an incorrect location estimate and consequent artifacts in the residual arrival times) and the strength of upper mantle heterogeneities (particularly near-source structures such as subducting slabs).…”
Section: Seismic Tomographymentioning
confidence: 99%
“…Initial investigations of aspherical structure in the lower mantle utilized moderate-sized (hundreds to a few thousand) sets of travel time anomalies (e.g., Sengupta and Toksoz, 1976) or differential travel time observations (e.g., Jordan and Lynn, 1974;Lay, 1983) to detect systematic variations relative to standard one-dimensional models. The main challenges in resolving lower mantle heterogeneity involve the uncertainty in earthquake source locations (typically, these are approximated by solving the location problem assuming a one-dimensional velocity structure, which intrinsically leads to an incorrect location estimate and consequent artifacts in the residual arrival times) and the strength of upper mantle heterogeneities (particularly near-source structures such as subducting slabs).…”
Section: Seismic Tomographymentioning
confidence: 99%
“…Seismic tomography has proved to be a powerful tool to provide information on the internal structure of the Earth and has done much to advance our understanding of its dynamics. Since its advent in the late 1970s [e.g., Aki et al , 1977; Sengupta and Toksöz , 1977; Dziewonski et al , 1977], seismic images have revealed features at a lateral and radial resolution that is continuously being improved [e.g., Ritsema et al , 2011]. …”
Section: Introductionmentioning
confidence: 99%
“…Early efforts to map the three-dimensional velocity structure of Earth [Aki et al, 1977;Dziewonski et al, 1977;Sengupta and Toksoz, 1976], all of which use a block parametrization, were limited in their structural detail by numerical methods that calculate the explicit inverse of the coefficient matrix. Early efforts to map the three-dimensional velocity structure of Earth [Aki et al, 1977;Dziewonski et al, 1977;Sengupta and Toksoz, 1976], all of which use a block parametrization, were limited in their structural detail by numerical methods that calculate the explicit inverse of the coefficient matrix.…”
Section: Introductionmentioning
confidence: 99%